ANALISIS KELAYAKAN PERENCANAAN PEMBANGUNAN JALAN PENGHUBUNG (MISSING LINK) ANTARA DESA SIKUR SAMPAI DESA PAOKMOTONG KABUPATEN LOMBOK TIMUR - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
In 2017, the Government of East Lombok plans to improve their public services, especially in the transportation sector related to the activation of the Paokmotong s new market. Thus government plans to build a connecting road in this national road. At the moment, the plan shows the highest v / c ratio at 0.51 and the busiest intersections with saturation degree at 0.76, which in the year of the plan would be arise as a new problem of transportation. This study includes road network analysis performance before and after the implementation of the road plan scenario. VISSIM software is used to support the trip assignment stage. By using this software, amount of technical aspects are examined include: the average speed of the network, travel time, trip distance, and average delay network. While in the Path Trace analysis also includes horizontal alignment, vertical alignment and layer of pavement plan. One more addition, is about economic factor. Economic development feasibility is done by comparing road construction costs and travel cost efficiencies through the project year which include: Net Present Value (NPV), Benefit Cost Ratio (BCR) and Internal Rate Return (IRR).